Lever les yeux de son livre, perdre le fil - Mireille Séguy (Revue des Langues Romanes)
The aim of this article is to revisit, through the prism of the notion of “rupture de lisibilité”, the cartography of the profane marvel as established by Francis Dubost in several seminal articles, essentially based on the analysis of the Lais and Chrétien's romances. Following in his footsteps, so to speak, I will ask whether the irruption of the marvel has the effect of breaking the legibility of the text in which it is embedded, and if so, in what ways and with what consequences for the reader's participation in the reflexive and sensitive elaboration of the meaning of what he or she reads. Ultimately, it will be a matter of defending the hypothesis that the unthinkable of marvel, in certain texts, does not call to be elucidated, evaded or surpassed, but on the contrary demands that we dwell on it, urging the reader to lift his eyes from his book and look elsewhere.